Geospatial Analysis of Time to Human Immunodeficiency Virus (HIV) Diagnosis and Adult HIV Testing Coverage Highlights Areas for Intervention in the US Southeast. (3rd March 2023) - Matthews, Lynn T; Long, Dustin M; Bassler, John; Nassel, Ariann; Levitan, Emily B; Heath, Sonya L; Rastegar, Jeremiah; Pratt, Madeline C; Kempf, Mirjam-Collette
Abstract: Background: In the United States (US), 44% of people with human immunodeficiency virus (PWH) live in the Southeastern census region; many PWH remain undiagnosed. Novel strategies to inform testing outreach in rural states with dispersed HIV epidemics are needed. Methods: Alabama state public health HIV testing surveillance data from 2013 to 2017 were used to estimate time from infection to HIV diagnosis using CD4 T-cell depletion modeling, mapped to county. Diagnostic HIV tests performed during 2013–2021 by commercial testing entities were used to estimate HIV tests per 100 000 adults (aged 15–65 years), mapped to client ZIP Code Tabulation Area (ZCTA). We then defined testing "cold spots": those with <10% adults tested plus either (1) within or bordering 1 of the 13 counties with HIV prevalence >400 cases per 100 000 population or (2) within a county with average time to diagnosis greater than the state average to inform testing outreach. Results: Time to HIV diagnosis was a median of 3.7 (interquartile range [IQR], 0–9.2) years across Alabama, with a range of 0.06–12.25 years. Approximately 63% of counties (n = 42) had a longer time to diagnosis compared to national US estimates. Six hundred forty-three ZCTAs tested 17.3% (IQR, 10.3%–25.0%) of the adult population from 2013 to 2017. To prioritize areas for testing outreach, we generated maps to describe 47 areas of HIV-testing cold spots at the ZCTA level. Conclusions: Combining public health surveillance with commercial testing data provides a more nuanced understanding of HIV testing gaps in a state with a rural HIV epidemic and identifies areas to prioritize for testing outreach. Abstract : Many people with HIV in the southeastern US remain undiagnosed. We used public and commercial datasets to estimate time from HIV infection to diagnoses by county and adult testing rates by ZIP Code Tabulation Area, which will inform testing outreach in Alabama.